Phenotype and Distribution of Immature Neurons in the Human Cerebral Cortex Layer II - Simona Coviello; Yaiza Gramuntell; Patrycja Klimczak; Patrycja Klimczak; Emilio Varea; José Miguel Blasco-Ibañez; Carlos Crespo; Antonio Gutierrez; Juan Nacher; Juan Nacher; Juan Nacher (Frontiers Media S.A., 2022)
This work provides evidence of the presence of immature neurons in the human brain, specifically in the layer II of the cerebral cortex. Using surgical samples from epileptic patients and post-mortem tissue, we have found cells with different levels of dendritic complexity (type I and type II cells) expressing DCX and PSA-NCAM and lacking expression of the mature neuronal marker NeuN. These immature cells belonged to the excitatory lineage, as demonstrated both by the expression of CUX1, CTIP2, and TBR1 transcription factors and by the lack of the inhibitory marker GAD67. The type II cells had some puncta expressing inhibitory and excitatory synaptic markers apposed to their perisomatic and peridendritic regions and ultrastructural analysis suggest the presence of synaptic contacts. These cells did not present glial cell markers, although astroglial and microglial processes were found in close apposition to their somata and dendrites, particularly on type I cells. Our findings confirm the presence of immature neurons in several regions of the cerebral cortex of humans of different ages and define their lineage. The presence of some mature features in some of these cells suggests the possibility of a progressively integration as excitatory neurons, as described in the olfactory cortex of rodents.